The effect of grazing system intensification on the growth and meat quality of beef cattle in the Brazilian Atlantic Forest biome. (May 2018) - Oliveira, P.P.A.; Corte, R.R.S.; Silva, S.L.; Rodriguez, P.H.M.; Sakamoto, L.S.; Pedroso, A.F.; Tullio, R.R.; Berndt, A.
Abstract: This study was carried out to evaluate the effects of four levels of intensification of grazing systems: 1) degraded pasture - DP; 2) irrigated pasture with high stocking rate - IHS; 3) dryland pasture with high stocking rate - DHS; 4) dryland pasture with moderate stocking rate - DMS; on growth, muscle development and meat quality of Nellore steers (271 ± 2.2 kg of live body weight - BW; 15 months old) during two consecutive periods (17 and 15 months). The final BW, the average daily BW gain, the hot carcass weight and the dress percentage were greater ( P  < 0.0001), and the ribeye area tended to be greater ( P  = 0.085), in the intensified systems compared to the degraded system. Animals in all systems presented similar back fat. Muscle development increased with the intensification of the grazing systems and meat quality was not affected. Highlights: Three levels of grazing system intensification and a degraded pasture Growth rate and muscle development increases as the intensification of pasture systems increases. The meat quality was similar for all grazing systems. Degraded pasture resulted in the lowest animal growth reflecting the inefficiency of the system. Grazing systems intensification have a land-saving effect.